Avaliação dos níveis de energia na dieta de cordeiros terminados em confinamento - Silva, Barbara Cristina Dantas da (2013)
The aim of this study was to evaluate the performance, feeding behavior, and carcass yields of Santa Inês lambs (SI) and ½ Dorper x Santa Inês (SI x D) feedlot and fed diets containing three levels of power (2.50, 2.79 and 3.03 Mcal / kg DM). We used 30 lambs, 15 of each genotype, with an average age of 120 days, in a completely randomized design in a 2 x 3 factorial design with 5 replications. Diets were isonitrogenous, containing 14% crude protein. The energy density of the diet affect the intake of dry matter and nutrients (P <0.05). Increased energy levels of diets improved weight gain, feed conversion and carcass hot and cold the animals studied as increased energy levels up. There was a positive effect (P <0.05) of the energy levels of the diets for the times when eating, ruminating and idling (h / day), intake and efficiency of rumination (kg DM / h). There was no effect (P <0.05) the energy level of the diets on intake and efficiency of rumination (NDF kg / h). With the increase of the energy levels of the diets had a positive influence on performance, feeding behavior, and carcass yield of feedlot lambs.